Efektivitas Pijat Endorphin dan Komunikasi Terapeutik terhadap Tingkat Kecemasan Inpartu Kala I - Marlina, Lina; Rahmawati, Ai; Daryanti, Eneng; Jamil, Maria Ulfah; Sulastri, Meti; Gustini, Sri (Universitas Malahayati, 2023)
ABSTRACT Childbirth is a natural occurrence that is experienced by every woman. In the process of childbirth, there will be a combination of physical processes and emotional experiences, causing anxiety. Anxiety can be overcome non-pharmacologically through relaxation. Relaxation can be in the form of endorphine massage or therapeutic communication. To determine the effectiveness of endorphin massage and therapeutic communication on anxiety levels in the first stage of labour. Used was quasi-experimental with a one group pretest posttest design. The population was all mothers who gave birth in the first stage at the Sukalaksana Health Center and Bungursari Health Center, using a quota sampling technique, namely at the Sukalaksana Health Center as many as 16 respondents with endorphine massage interventions, Bungursari Health Center 16 respondents with therapeutic communication techniques. Before and after the intervention, the HARS anxiety scale questionnaire was given. Data analysis used paired t test. Anxiety research before the intervention found that all mothers who gave birth experienced anxiety, and the highest was in the moderate category with 18 people (56.25%). After treatment, the highest anxiety level in therapeutic communication respondents, namely the moderate category, was 12 people (75%), the most endorphine massage respondents were in the moderate category, 13 people (81.25%). There is an effect of therapeutic communication and endorphine massage on anxiety levels with a ρvalue below 0.05, namely the therapeutic communication group 0.001 and the endorphine massage group 0.002. Endorphine massage reduced anxiety levels more because the average anxiety level of the therapeutic communication group was higher (5.8125) than the endorphine massage group (5.3750) Keywords : Endorphin Massage, Therapeutic Communication, Anxiety, Labour ABSTRAK Persalinan merupakan kejadian alamiah yang dialami setiap perempuan. Pada proses persalinan, akan terjadi sebuah kombinasi antara proses fisik dan pengalaman emosional, sehingga menimbulkan kecemasan. Kecemasan dapat diatasai secara non farmakologi melalui relaksasi. Relaksasi bisa berupa pijat endorphine maupun komunikasi terapeutik. Untuk mengetahui efektivitas pijat endorphin dan komunikasi terapeutik terhadap tingkat kecemasan inpartu kala I. Metode penelitian yang digunakan adalah quasi eksperimen dengan desain one group pretest posttest. Populasinya adalah seluruh ibu yang melahirkan kala I di Puskesmas Sukalaksana dan Puskesmas Bungursari, dengan teknik quota sampling, yaitu di Puskesmas Sukalaksana sebanyak 16 responden dengan intervensi pijat endorphine, Puskesmas Bungursari 16 responden dengan teknik komunikasi teurapeutik. Sebelum dan sesudah intervensi, diberikan kuesioner skala kecemasan HARS. Analisis data menggunakan uji paired t test. Hasil penelitian kecemasan sebelum intervensi diperoleh bahwa semua ibu melahirkan mengalami kecemasan, dan paling tinggi ada pada kategori sedang sebanyak 18 orang (56.25%). Setelah perlakuan, tingkat kecemasan pada responden komunikasi terapeutik paling banyak yaitu kategori sedang sebanyak 12 orang (75%), pada responden pijat endorphine paling banyak kategori sedang sebanyak 13 orang (81.25%). Terdapat pengaruh komunikasi terapeutik dan pijat endorphine terhadap tingkat kecemasan dengan ρvalue dibawah 0,05 yaitu kelompok komunikasi terapeutik 0,001 dan kelompok pijat endorphine 0,002 . Pijat endorphine lebih menurunkan tingkat kecemasan karena rata-rata tingkat kecemasan kelompok komunikasi terapeutik lebih tinggi (5,8125) dibandingkan kelompok pijat endorphine (5,3750) Kata Kunci: Pijat Endorpin, Komunikasi Terapeutik, Kecemasan, Inpartu